Comparing the quality of experiences of athletes with a disability at two high-performance talent identification - Lawson, J. A.; Davey, J.; Bruce, J.; Baker, J.; Latimer-Cheung, A. E. (2019 SCAPPS Conference. Vancouver, BC, Canada, October 17 -19, 2019, 2019)
Two approaches to high-performance talent identification events for athletes with a disability (AWAD) are for participants to: 1) perform physically demanding tests, or 2) try different sports. Athletes` quality of experience at these events may influence their pursuit of Para sport; however, the impact of these differing event formats on experience quality is unknown. Objective: To compare the experiences of AWAD between high-performance talent identification events. Participants: Twenty individuals with physical and/or visual impairments (Mage=30.39, SD=13.755; 45% Female) who attended one of two four-hour talent identification events were recruited. Methods: Pre-post measures of quality experience assessed participants` feeling states, event enjoyment, and intentions to pursue Para sport. Data were analyzed using repeated measures analysis of variance and independent t-tests. Results: Feelings of autonomy, belonging, and engagement increased following the events, ps=<.05. Physical test participants reported greater feelings of challenge and meaning than try-it event participants, F(1,18) = 5.521, p=<.05; F(1,18) = 4.689, p=<.05. No time by event interactions were observed except for feeling state, F(1,18) = 4.355, p=<.05. Positive feelings increased over time among try-it style event participants, p=<.05. T-tests revealed no difference in intentions to participate in, or seek information on, Para sport; or to pursue opportunities if identified as having Paralympic potential (ps<.05). Physical test participants reported higher intentions to pursue new Para sport opportunities offered than try-it event participants, t(2.76)=.016, p<.05. Conclusion: Participation in a high-performance talent identification event for AWAD fosters elements of quality participation; however, event structure influences some elements, including challenge, meaning, and feelings